Blurring image quality assessment method based on histogram of gradient - Ahn, Sangwoo; Park, Jongjoo; Chong, Jongwha (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
In this paper we propose a blurring image quality assessment (IQA) based on histogram of oriented gradients (HOG). The image quality can be determined by the slope value of the HOG of the target image. The representative line of HOG is approximated by a random sample consensus set (RANSAC). Simulation results performed on the LIVE image quality assessment database show that the proposed method aligns better with how the human visual system perceives image quality than several state-of-the-art IQAs.